Technical and economical performance of parabolic trough collector power plant under Algerian climate - Yousfi, Mohamed Lamine; Zaaraoui, Abdelkader; Said, Noureddine (Procedia engineering, 2012)
Parabolic trough solar technology has been proven at nine commercial Solar Electric Generating System (SEGS) power plants that are operating in the California Mojave desert. Simulation using different models when planning this kind of projects and choose the best site for this technology minimizes the risks of these projects. For this purpose, a detailed performance model of the 30 MW SEGS VI parabolic trough power plant was created in the TRNSYS simulation environment using the Solar Thermal Electric Component model library. Both solar and power cycle performance were modeled, but natural gas-fired hybrid operation was not. Good agreement between model predictions and plant measurements was found, with errors usually less than 10%. Also, an economical study has been established to determine the best site, based on the cost of electricity generation. The result shows that Bechar's site is the best site for this technology because of its lowest levelzed electricity cost and its high irradiance level. While the model could be improved, it demonstrates the capability to perform detailed analysis for this technology.
Keywords: Solar thermal power plant; TRNSYS simulation; parabolic trough collector; Renewable energy; SEGS VI